Which support for severe ankle sprain promotes fastest functional recovery? - Lamb, S. E.; Marsh, J. L.; Hutton, J. L.; Nakash, R.; Cooke, M. W. (The Lancet, 2010)
BACKGROUND: Severe ankle sprains are a common presentation in emergency departments in the UK. We aimed to assess the effectiveness of three different mechanical supports (Aircast brace, Bledsoe boot, or 10-day below-knee cast) compared with that of a double-layer tubular compression bandage in promoting recovery after severe ankle sprains. METHODS: We did a pragmatic, multicentre randomised trial with blinded assessment of outcome. 584 participants with severe ankle sprain were recruited between April, 2003, and July, 2005, from eight emergency departments across the UK. Participants were provided with a mechanical support within the first 3 days of attendance by a trained health-care professional, and given advice on reducing swelling and pain. Functional outcomes were measured over 9 months. The primary outcome was quality of ankle function at 3 months, measured using the Foot and Ankle Score; analysis was by intention to treat. This study is registered as an International Standard Randomised Controlled Trial, number ISRCTN37807450. RESULTS: Patients who received the below-knee cast had a more rapid recovery than those given the tubular compression bandage. We noted clinically important benefits at 3 months in quality of ankle function with the cast compared with tubular compression bandage (mean difference 9%; 95% CI 2.4-15.0), as well as in pain, symptoms, and activity. The mean difference in quality of ankle function between Aircast brace and tubular compression bandage was 8%; 95% CI 1.8-14.2, but there were little differences for pain, symptoms, and activity. Bledsoe boots offered no benefit over tubular compression bandage, which was the least effective treatment throughout the recovery period. There were no significant differences between tubular compression bandage and the other treatments at 9 months. Side-effects were rare with no discernible differences between treatments. Reported events (all treatments combined) were cellulitis (two cases), pulmonary embolus (two cases), and deep-vein thrombosis (three cases). INTERPRETATION: A short period of immobilisation in a below-knee cast or Aircast results in faster recovery than if the patient is only given tubular compression bandage. We recommend below-knee casts because they show the widest range of benefit. FUNDING: National Co-ordinating Centre for Health Technology Assessment.